Acceptability of and Willingness to Use Virtual Reality Exergames for Weight Loss Among Young Adults With Overweight or Obesity in China: Qualitative Study - Yanya Chen; Bingsheng Guan; Yaqi Zhang; Suen Chow Lee; Jia-yu Liu; Sicun Li; Ming Liu; Xiaoshen Zhang; Wai-kit Ming (JMIR Serious Games)
Abstract BackgroundOverweight and obesity seriously affect physical and psychological health worldwide. They are common public health issues in young adults who are considered a “vulnerable group” prone to adopt unhealthy lifestyles that can lead to overweight and obesity. Virtual reality exergames could help increase balance performance among patients with Parkinson disease and improve depression and pain interference among individuals with chronic neck pain. Still, limited research has been conducted on the use of virtual reality exergames among young adults with overweight and obesity, and their willingness and acceptability remain unclear. ObjectivesThis study aimed to assess the acceptability of and willingness to use virtual reality exergames for weight loss among young adults with overweight or obesity. MethodsThis was a qualitative study. Sixteen young adults with overweight or obesity were recruited in Guangzhou, China, and divided into 4 focus groups. They were interviewed between September and October 2023 through semistructured interviews. NVivo (version 14; Lumivero) was used to transcribe, code, and thematically analyze interviews. ResultsFour main themes and 8 subthemes emerged from the data. The main themes included perception of previous weight loss measures (regarded exercise and diet as the main measures for weight loss and difficulties in holding on to the weight loss methods), acceptability of virtual reality exergames (increasing opportunities for exercise, a powerful means for propelling doing exercise, positive impact on psychological well-being, and more appealing to office workers than students), willingness to use virtual reality exergames, and concerns (weight loss effect and other concerns). ConclusionsVirtual reality exergames were seen as beneficial for maintaining exercise and promoting psychological well-being among young adults with overweight or obesity, despite concerns about effectiveness, cost, and privacy. Almost all young adults indicated their willingness to try these kinds of games if given the opportunity. These findings suggested that virtual reality exergames could be a promising tool for weight management in this population.